2017
DOI: 10.12659/ajcr.905671
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Giant Basal Cell Carcinoma of the Abdominal Wall: Excision and Immediate Reconstruction with a Pedicled Deep Inferior Epigastric Artery Perforator (DIEP) Flap

Abstract: Patient: Female, 82Final Diagnosis: Giant basal cell carcinomaSymptoms: AnemiaMedication: —Clinical Procedure: —Specialty: Plastic SurgeryObjective:Rare diseaseBackground:Basal cell carcinoma (BCC) greater than 5 cm in diameter is called giant basal cell carcinoma (GBCC), or super giant basal cell carcinoma if it has a diameter larger than 20 cm. Giant BCC only accounts for 0.5% of BCCs and super giant BCC is exceedingly rare. On account of their rarity, there are no established guidelines for GBCC treatment.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…1,3 In contrast to the very low metastatic incidence of BCCs overall (0.03%), the rate has been reported to be as high as 45% in tumors greater than 10 cm and 100% in tumors greater than 25 cm. 11 The most common sites of metastasis are the lymph nodes and lungs, with a mean survival after metastatic spread of only 8-14 months. 11,12 Although minor bleeding has been associated with BCCs secondary to tissue friability common to these neoplasms, only 10 cases of acute or chronic anemia subsequent to giant BCC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 In contrast to the very low metastatic incidence of BCCs overall (0.03%), the rate has been reported to be as high as 45% in tumors greater than 10 cm and 100% in tumors greater than 25 cm. 11 The most common sites of metastasis are the lymph nodes and lungs, with a mean survival after metastatic spread of only 8-14 months. 11,12 Although minor bleeding has been associated with BCCs secondary to tissue friability common to these neoplasms, only 10 cases of acute or chronic anemia subsequent to giant BCC have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 Literature review found only 11 cases reported. 2,3 In contrast to BCCs, which are often found in the sun-exposed areas of the head and neck, GBCCs are located predominantly on the back, where they go unnoticed by the patient and can remain hidden under clothing. 4 There is a greater propensity for metastasis, particularly after reaching a size of 10 cm.…”
Section: Discussionmentioning
confidence: 99%
“…These risk factors are shared by GBCC, but larger tumors have additional risk factors including an aggressive histological subtype, recurrence after previous treatment, a history of radiation exposure, or a history of neglect. 3 They are most often reported in those with low socioeconomic status, and physical or mental disability which impedes access to health care. 4 Autism has been found to obstruct use of healthcare through several mechanisms, including fear or anxiety, difficulty communicating with the practitioner, and sensory difficulties with the busy clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Neglect is responsible for one third of the case of giant basal cell carcf. Some authors have suggested that Giant basal cell carcinoma is cigarette smoking-related in more than 50% of the cases [5].Giant BCC could sometimes show an aggressive behavior [6][7]. Giant BCC is a rare variant that infiltrated dermis and frequently involves extradermal structures [6].…”
Section: Sirmentioning
confidence: 99%
“…Giant BCC should be treated aggressively and closely monitored. Treatment relies mainly on surgery with wide local excision usually followed by reconstruction with skin grafts or free flaps [6]. Giant BCC is rarely reported in the literature.…”
Section: Sirmentioning
confidence: 99%